Internalized stigma among pediatric patients with osteosarcoma and retinoblastoma in Guatemala, Jordan, and Zimbabwe - Williams, Anneliese H.; Velasquez, Thelma; Chitsike, Inam; Halalsheh, Hadeel; Cáceres-Serrano, Ana; Fuentes, Lucia; Chokwenda, Nester; Ferrara, Gia; Wardell, Joseph; Bilbeisi, Tharwa; Matsikidze, Edith; Bhakta, Nickhill; et al. (Frontiers in Oncology, 2026)
IntroductionInternalized stigma adversely impacts childhood cancer survivors, limiting their ability to reintegrate with their communities and maintain social networks. However, the impact of internalized stigma on children undergoing cancer treatment is unknown, and no interventions exist to mitigate it. The Activating Events-Beliefs-Consequences (ABC) model from Cognitive Behavioral Theory (CBT) has been used to analyze internalized stigma and inform interventional work. This study employs the ABC model as a conceptual framework to explore how internalized stigma manifests for children recently diagnosed with osteosarcoma and retinoblastoma in Guatemala, Jordan, and Zimbabwe.MethodsWe conducted semi-structured interviews with nine adolescent patients (aged 12-18), 28 caregivers, and 19 clinicians at tertiary cancer centers in Guatemala, Jordan, and Zimbabwe. Interviews occurred in Spanish, Arabic, Shona, and English and were transcribed and translated into English for analysis. Two coders independently coded transcripts, resolving disagreements through consensus and third-party adjudication. A framework analysis used the ABC model to understand manifestations of internalized stigma, defined a priori as “a patient’s own adoption of negative societal beliefs or feelings, including changes in self-identification.”ResultsPatients, caregivers, and clinicians all described internalized stigma in pediatric cancer patients. Cancer-related physical changes and community stigma activated internalized stigma. Patients responded to these events by forming beliefs about their appearance, abilities, normalcy, and future, which shaped their behaviors and emotions. While some patients internalized stigmatizing beliefs about themselves and experienced negative consequences, others maintained resilient self-beliefs that fostered adaptive behaviors and emotions. Knowledge about the disease, supportive interactions with survivors and other patients, and caregiver support promoted stigma resilience.DiscussionOur results demonstrate that internalized stigma impacts pediatric cancer patients from the time of diagnosis, highlighting the relevance of the ABC model in understanding this complex phenomenon. Our findings suggest CBT-based interventions that target patient beliefs, address identified activating events, and enhance multilevel support could help mitigate internalized stigma in pediatric cancer patients. Additional research should explore the efficacy of such interventions, the transferability of our findings to children with other cancer diagnoses and to various geographies, as well as how internalized stigma evolves across the cancer continuum.